2005
DOI: 10.2165/00148581-200507030-00005
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of Cancer Chemotherapy

Abstract: Many children and adolescents with cancer receive chemotherapeutic agents that are cardiotoxic. Thus, while survival rates in this population have improved for some cancers, many survivors may experience acute or chronic cardiovascular complications that can impair their quality of life years after treatment. In addition, cardiac complications of treatment lead to reductions in dose and duration of chemotherapy regimens, potentially compromising clinical efficacy. Anthracyclines are well known for their cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
134
0
4

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 125 publications
1
134
0
4
Order By: Relevance
“…• Introduction of extended-field high-dose (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) The types of chemotherapy-induced cardiovascular alterations reported primarily, but not exclusively, in adults include the following: Acute cardiac rhythm abnormalities (arrhythmias including QT prolongation), myocardial ischemia or infarction, hypertension, and significant left ventricular (LV) contractile dysfunction. 37,38 The pathogenesis of these diverse cardiovascular effects varies and may involve multiple mechanisms.…”
Section: Pathophysiology Of Cardiovascular Toxicity Pathophysiology Omentioning
confidence: 99%
See 2 more Smart Citations
“…• Introduction of extended-field high-dose (35)(36)(37)(38)(39)(40)(41)(42)(43)(44) The types of chemotherapy-induced cardiovascular alterations reported primarily, but not exclusively, in adults include the following: Acute cardiac rhythm abnormalities (arrhythmias including QT prolongation), myocardial ischemia or infarction, hypertension, and significant left ventricular (LV) contractile dysfunction. 37,38 The pathogenesis of these diverse cardiovascular effects varies and may involve multiple mechanisms.…”
Section: Pathophysiology Of Cardiovascular Toxicity Pathophysiology Omentioning
confidence: 99%
“…37,38 The pathogenesis of these diverse cardiovascular effects varies and may involve multiple mechanisms.…”
Section: Pathophysiology Of Cardiovascular Toxicity Pathophysiology Omentioning
confidence: 99%
See 1 more Smart Citation
“…Long-term cardiac complications may occur several years after completion of anticancer treatment [1][2][3][4][5][6]. In the past year report from the Childhood Cancer Survivor Study (the largest cohort of childhood cancer survivors in the world) showed that survivors of childhood cancers are five to ten times more likely than their healthy siblings to develop heart disease even 30 years after diagnosis -such as congestive heart failure, myocardial infarction, pericardial disease, valvular heart disease [2].…”
mentioning
confidence: 99%
“…[13][14][15][16] Early-onset cardiotoxicity occurs within 1 year after therapy, 14,15,[17][18][19][20] and late-onset cardiotoxicity occurs >1 year after anthracycline therapy. 14,15,[18][19][20] Thus, the report by Sawaya et al 7 is limited to predicting early-onset cardiotoxicity. As it may not be long enough for clinically relevant events to develop, the utility for predicting events in this short period is unknown.…”
Section: Circ Cardiovasc Imagingmentioning
confidence: 99%